Pengaruh DER, EPS, dan ROA Terhadap Harga Saham pada Perusahaan Properti dan Real Estate yang Terdaftar di BEI - Citra Putriana Dewi; Leni Nur Pratiwi; Banter Laksana (Indonesian Journal of Economics and Management, 2021)
This study aims to determine the effect of DER,EPS and ROA on stock prices in Property and Real Estate Companies listed on the Indonesia Stock Exchange (IDX) in 2015 – 2019.The population in this study is 28 company using purposive sampling technique. The data analysis method used is Multiple Linear Regression Analysis using IBM SPSS 25 software .The results showed that the variables DER, EPS, and ROA simultaneously had positive and significant effect on stock prices. DER partially has a negative and insignificant effect on stock prices. EPS partially positive and significant effect on stock prices. ROA partially has a negative and significant effect on stock prices.